SARS-CoV-2 Vaccine Effects on Semen Parameters: A Systematic Review and Meta-Analysis (2022)
ABSTRACT: Objective: Vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epitomizes the best preventative SARS-CoV-2 infection strategy to counteract the severe consequences of infection. However, concerns have been raised that the vaccines could have an adverse effect on sperm function and overall reproductive health. This combined systematic review and meta-analysis aimed to investigate the effects of different available SARS-CoV-2 vaccines on semen parameters. Methods: A systematic PubMed, Scopus, Google Scholar, ScienceDirect, LILACS (Literatura Latinoamericana y del Caribe en Ciencias de la Salud), and Scilit database literature search until mid-June 2022 was conducted. Prospective and retrospective studies were eligible. No limitation was placed on language. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were thereafter obtained. Results: Upon search completion, 122 studies were identified and retrieved and 110 were excluded, while the remaining 12 independent studies evaluating the effects of coronavirus disease 2019 (COVID-19) vaccines on semen parameters were included in this review. The total number of men included was 1551, aged 22.4-48 years. Following meta-analysis, the SMD summary measure with 95% CI for each semen parameter included a concentration of 0.22 (0-0.22); Total sperm count of 0.11 (0.18-0.24); Total motility of 0.02 (0.05-0.09); Volume of 0.02 (-0.1-0.14); Vitality of 0.55 (-0.19-0.29), progressive motility of -0.43 (-0.54 to -0.32); Total motile sperm count of -0.38 (-0.44 to -0.31); And normal morphology of 0.42 (-0.54 to -0.3). In brief, the total sperm count was slightly increased post-vaccination, while progressive motility, total motile sperm count, and normal morphology were marginally reduced post-vaccination, according to the meta-analysis. Conclusions: No effects were observed regarding sperm viability and semen volume since the results of all the studies crossed the line of no effect. All seminal parameters analyzed showed a negligible or small change in relation to the vaccination effect. Furthermore, the parameters remained within the normal World Health Organization reference ranges, making the clinical significance unclear. Therefore, based on these results, it appears that vaccination does not have negative effects on semen quality. The individual study findings suggested that COVID-19 vaccines are not associated with decreased semen parameters.